(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This journal article is the result of an interdisciplinar research project whose main findings have been recently published as a book entitled Mujeres en los gobiernos locales. The focus of this article is on the first women to be appointed mayoresses in Spain during the Primo de Rivera dictatorship and on the eve of the Second Republic (from 1924 to 1930). It highlights the circumstances that led to their designation, the criteria that were required in order to become mayoress, and the tasks that were undertaken by them at the local government level.